Species Diversity of Trees in Sungai BuluhPeat Forest Reserve, Mendahara UluDistrict, Tanjung Jabung Timur Regency - Hafizah Nahlunnisa; Nursanti Nursanti; Fawwaz Dinanty; Wahyu Nazri Yandi (Forestry Department, University of Muhammadiyah Makassar, 2025)
Peat swamp forests are ecologically important ecosystems that regulate hydrology, store carbon, and support high biodiversity. The Sungai Buluh Peat Forest Reserve in Mendahara Ulu District, Tanjung Jabung Timur, Jambi Province, Indonesia, represents a relatively undisturbed tropical peat swamp forest with high potential for tree species diversity. This study assessed tree species composition, diversity, and community structure in the Sinar Wajo and Sungai Beras Village Forests to support ecological monitoring and guide sustainable forest. Species dominance was analyzed using the Importance Value Index (IVI), while community structure was evaluated using the Shannon–Wiener diversity index (H′), Pielou’s evenness (E), Margalef’s richness (Dmg), and community similarity (IS). A total of 45 species from 22 families were recorded in Sinar Wajo Village Forest, while 36 species from 21 families were documented in Sungai Beras Village Forest. Diversity and richness were higher in Sinar Wajo village forest, while both sites exhibited high evenness and low dominance, indicating stable and heterogeneous communities. Community similarity between the two forests was high, suggesting comparable ecological and environmental conditions. These results provide a comprehensive overview of tree species composition and community structure in the Sungai Buluh Peat Forest Reserve. The study emphasizes the importance of baseline ecological data to guide sustainable forest management and conservation, supporting biodiversity preservation and maintaining ecosystem functions in tropical peat swamp forests.